2021
DOI: 10.3390/molecules26185709
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Effect on Aβ-Induced Alzheimer’s Mice by Litsea cubeba Persoon Powder

Abstract: Alzheimer’s disease (AD) is caused by excessive oxidative damage and aging. The objective of this study was to investigate the anti-dementia effect of LCP fruit powder on amyloid β (Aβ)-induced Alzheimer’s mice. The composition of LCP essential oil was determined by gas chromatography/mass spectrometry. In addition, the water maze was used to evaluate the learning and memorizing abilities of the mice. The concentrations of malondialdehyde (MDA), protein carbonyl, phosphorylated τ-protein, and the deposition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Moreover, it appears that the aggregation of Tau protein, the reduction of ACh, and the deposition of Aβ are also related to high oxidative stress. High oxidative stress has been shown to promote the deposition of Aβ42 and lead to the hyperphosphorylation of Tau protein, which could result in the instability and dissociation of the microtubules in the brain and ultimately lead to the oligomerization of Tau protein . The oxidative stress has also been considered a key modulator in neurodegenerative diseases, including AD .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it appears that the aggregation of Tau protein, the reduction of ACh, and the deposition of Aβ are also related to high oxidative stress. High oxidative stress has been shown to promote the deposition of Aβ42 and lead to the hyperphosphorylation of Tau protein, which could result in the instability and dissociation of the microtubules in the brain and ultimately lead to the oligomerization of Tau protein . The oxidative stress has also been considered a key modulator in neurodegenerative diseases, including AD .…”
Section: Discussionmentioning
confidence: 99%
“…High oxidative stress has been shown to promote the deposition of Aβ42 54 and lead to the hyperphosphorylation of Tau protein, which could result in the instability and dissociation of the microtubules in the brain and ultimately lead to the oligomerization of Tau protein. 54 The oxidative stress has also been considered a key modulator in neurodegenerative diseases, including AD. 30 In this study, the results showed that parapyruvate could induce the aggregation of Tau and p-Tau, and the increase of the AChE activity, supporting the crucial role of the oxidative stress in the etiology of AD.…”
Section: Discussionmentioning
confidence: 99%
“… Jeon et al (2011) found that early inhalation of SHXW EO improved CI caused by Aβ (1–42) and inhibited Aβ-induced Tau phosphorylation by suppressing the activation of JNK and p38 in the brain. Lee et al (2021) fed AD mice Induced by Aβ1-40 with the same essential oil content of Litsea cubeba Persoon Powder, and showed that it reduced P-Tau content and Aβ plaques, resulting in about 3–8% reduction in brain atrophy.…”
Section: Mechanism Of Volatile Oil For Cognitive Impairmentmentioning
confidence: 99%
“…It is called “Shan Cang Zi or shan jiao ji” in China and “makauy” in Taiwan. The indigenous people in Taiwan used the essential oil of L. cubeba to cure headaches, inflammation, intoxication, bronchitis, and dyspepsia [ 52 ]. The effect of L. cubeba essential oil has been studied in Ab-induced AD mice and revealed decreasing oxidative stress, brain atrophy, and Aβ plaques.…”
Section: P Athology Of Alzheimer’s Diseasementioning
confidence: 99%
“…The effect of L. cubeba essential oil has been studied in Ab-induced AD mice and revealed decreasing oxidative stress, brain atrophy, and Aβ plaques. Besides, oral administration of L. cubeba (30.2 mg/day) for 8 weeks could improve spatial and working learning and memory deficit in Ab-induced AD mice [ 52 ]. The L. cubeba essential oil also displayed its effect on anxiolytic and analgesic activities and prolonged sleeping in ICR mice [ 53 ].…”
Section: P Athology Of Alzheimer’s Diseasementioning
confidence: 99%